A Simple Fabrication Process Based on Micro-masonry for the Realization of Nanoplate Resonators with Integrated Actuation and Detection Schemes - Bhaswara, Adhitya; Keum, Hohyun; Mathieu, Fabrice; Legrand, Bernard; Kim, Seok; Nicu, Liviu; Leïchlé, Thierry (Frontiers in Mechanical Engineering, 2016)
In this work, we use the micro-masonry technique to fabricate nanoplate resonators with integrated electrostatic actuation and capacitive detection in a few steps. Our approach is an alternative solution to the current fabrication methods used to create membranes and plates that usually rely on the selective etching of a sacrificial layer. Highly doped silicon plates were transfer-printed using microtip elastomeric stamps onto insulated bases displaying cavities in order to form suspended structures with airtight gaps. By post-processing adequate interconnections, the fabricated resonators were actuated and their resonant frequency measured in a fully integrated manner. The tested nanoplate devices behave as predicted by theory and offer quality factors of more than 30 in air. Because the cavities used for electrostatic actuation/sensing of the devices are tight sealed, nanoplates fabricated via micro-masonry are suitable for liquid environment operation and are thus a promising solution for biosensing applications.